2021
DOI: 10.3389/fnsys.2020.590231
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Spinal Epidural Stimulation-Enabled Stepping by Descending Intentional Motor Commands and Proprioceptive Inputs in Humans With Spinal Cord Injury

Abstract: Background: Regaining control of movement following a spinal cord injury (SCI) requires utilization and/or functional reorganization of residual descending, and likely ascending, supraspinal sensorimotor pathways, which may be facilitated via task-specific training through body weight supported treadmill (BWST) training. Recently, epidural electrical stimulation (ES) combined with task-specific training demonstrated independence of standing and stepping functions in individuals with clinically complete SCI. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 58 publications
0
14
0
1
Order By: Relevance
“…However, unexpected recovery of volitional lower limb movement with scES in supine position was also observed in individuals with clinically motor complete SCI (Harkema et al 2011;Angeli et al 2014). Our research group and others subsequently showed that supraspinal inputs can also be integrated by the spinal circuitry together with peripheral sensory information during weight-bearing standing and stepping, modulating the motor pattern promoted by scES (Angeli et al 2014;Grahn et al 2017;Rejc and Angeli 2019;Gill et al 2020). Volitional intent to contribute to motor pattern generation was a key component in the recovery of walking in individuals with motor complete SCI (Angeli et al 2018;Gill et al 2018).…”
Section: Introductionmentioning
confidence: 71%
“…However, unexpected recovery of volitional lower limb movement with scES in supine position was also observed in individuals with clinically motor complete SCI (Harkema et al 2011;Angeli et al 2014). Our research group and others subsequently showed that supraspinal inputs can also be integrated by the spinal circuitry together with peripheral sensory information during weight-bearing standing and stepping, modulating the motor pattern promoted by scES (Angeli et al 2014;Grahn et al 2017;Rejc and Angeli 2019;Gill et al 2020). Volitional intent to contribute to motor pattern generation was a key component in the recovery of walking in individuals with motor complete SCI (Angeli et al 2018;Gill et al 2018).…”
Section: Introductionmentioning
confidence: 71%
“…Each gait cycle duration was identified by Tekscan in-shoe sensors. The stance and swing phase of the gait cycle were identified similar to our previous publication (7). The duration of the applied force was identified through FSRs and a minimum threshold of 5 N determined initiation and termination of assistance.…”
Section: Data Processingmentioning
confidence: 94%
“…Study participants sustained an SCI at least two years prior to study enrollment. Two study participants were part of a study at the Mayo Clinic whose functional motor responses have previously been reported [ 4 , 7 , 13 , 30 , 31 ]. These publications focused on motor outputs during functional tasks such as voluntary control of lower-extremity muscles, stepping, standing, and sitting [ 7 , 13 , 30 , 31 ], as well as intraoperative recordings [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…Two study participants were part of a study at the Mayo Clinic whose functional motor responses have previously been reported [ 4 , 7 , 13 , 30 , 31 ]. These publications focused on motor outputs during functional tasks such as voluntary control of lower-extremity muscles, stepping, standing, and sitting [ 7 , 13 , 30 , 31 ], as well as intraoperative recordings [ 4 ]. All data and analyses from these participants in this report were recorded at low (0.2–2 Hz) non-functional stimulation frequencies while the subjects were supine.…”
Section: Methodsmentioning
confidence: 99%